Juridical Study With Deed Of Under Hand Evidence Which Notarized In Completion Case In Court - Eko Nurhanafi; Akhmad Khisni; Amin Purnawan (Jurnal Akta, 2020)
This study aims to assess and analyze: 1). Notary form of responsibility for the validity of the deed under which legalized hand. 2). The strength of evidence by deed under the hand which has been legalized by the Notary in settling disputes in court. 3). The authority of the judge in dismissing deed under the hand that had to notarize a Notary.Research using normative juridical, The collection of primary and secondary data obtained by interview and literature study, then analyzed by qualitative analysis method.Based on the results of this study concluded that: 1). Notary form of responsibility for the validity of the deed under which legalized hand there is the certainty that the signature means certain that the signature was indeed the parties to the agreement and not others. It is said that because of legalizing the letter should be required to know the people who are signing an a way to see his ID such as Identity Card and others. 2). The strength of evidence by deed under the hand which has been legalized by the Notary in settling disputes in court that the evidence is perfect as an authentic deed. Deed under the hand that has obtained the legalization of Notaries has the strength of evidence was perfect, because the deed under the hand of the truth lies in the signatures of the parties. So with the recognition of such signatures, then the contents of the deed was regarded as an agreement between the parties. 3) The authority of judges to cancel the deed under the hand that had to notarize the notary is a judge can only do that if put to him a certificate as evidence. The judge on his own initiative may not make a decision without their deed as evidence written agreement.Keywords: Notary; Strength of Evidence; Deeds Under Hand